Pancytopenia: the perspective from Western Gujarat, India - Deshpande, Shubhangi V.; Godbole, Varsha Y.; Asher, Archana D. (International Journal of Advances in Medicine, 2019)
Background: Pancytopenia is one of the common laboratory findings in patients presenting to us with varied clinical presentations. Risks of untreated Pancytopenia are high causing anxiety to treating doctors and patients alike. It also involves long list of investigations including a very painful marrow biopsy, life-threatening complications and treatment involves multiple blood component therapy. A total of 101 cases of pancytopenia over a period of 1 year were analysed retrospectively to find i) commonest presenting symptoms ii) commonest cause of pancytopenia, response to treatment iii) Depending on the cause, to consider if any measures can be taken for prevention Methods: Cross sectional study of 101 admitted patients of Pancytopenia on the basis of information extracted from the case sheets. The data was analyzed and presented as frequencies and Percentages. Results: Out of 101 cases analysed, 53 (52.47%) were females 48 (47.52%) patients males. Fatigue 74 patients (73.2%) was the commonest presenting symptom followed by fever 33 (32.6%), breathlessness 13 (12.87%) and bleeding 4(3.8%). Vitamin B12 deficiency 58 (57.6%) patients showed and was the commonest cause of pancytopenia. Infections in 24 (23.7%) like malaria16 (15.6%), dengue 5 (4.96%), PLHA 1(0.96%) and hepatitis B 2 (1.96%) was the second common cause in present study. Recovery of pancytopenia was prompt in Malaria Dengue. HIV, Hepatitis B viral infection showed persistent pancytopenia with hypoplastic marrow. Chronic liver disease portal hypertension splenomegaly accounted for 9 (8.9%) patients. Drug induced marrow suppression due to ongoing treatment for underling disease resulted in pancytopenia in 4 (3.96%) patients. Aplastic anaemia in3 (2.9%), myelodysplastic syndrome 2 (1.9%) and acute leukaemia 1 (0.96%) were the less common causes. Conclusions: Commonest symptom on presentation were related more to anaemia than to neutropenia and thrombocytopenia. megaloblastic anaemia due to Vitamin B12 deficiency was the leading reversible cause of pancytopenia in present study followed by infections like Malaria Dengue. Gujarat, India being predominantly vegetarian state, local dietary habits are thought to be responsible for inadequate B12 daily consumption, hence we suggest fortifying the daily diet with B12 supplementation at a larger scale just like iodisation of salt to counter iodine deficiency.